The life of Buddhism - Reynolds, Frank, 1930-; Carbine, Jason A., 1971- (University of California Press, 2000)
Bringing together fifteen essays by outstanding Buddhist scholars from Asia, Europe, and North America, this book offers a distinctive portrayal of the "life of Buddhism." The contributors focus on a number of religious practices across the Buddhist world, from Sri Lanka to New York, Japan to Tibet.
Keywords: Buddhism.; Religious life -- Buddhism.; Buddhism -- Customs and practices.; Bouddhisme.; Bouddhisme -- Coutumes et pratiques.; Vie religieuse -- Bouddhisme.; RELIGION -- Buddhism -- General.; Buddhism; Buddhism -- Customs and practices; Religious life -- Buddhism; Humaniora -- Religionsvidenskab.